Oral Story of Women’s Anti-mining Group in Sumba: A Narrative of Subaltern Movement for Food Sovereignty - Titiek Kartika Hendrastiti (Jurnal Perempuan, 2019)
This article analyses the meaning of the tutur of the female anti-gold mining troop from Praikaroku Jangga Village, Central Sumba Regency, East Nusa Tenggara. This manuscript is important, because there are a lot of women's activisms at the local level that are not recorded in the history of women's movements in the post-1998 Indonesian reformation. This study is a postcolonial feminist ethnography, where the main basis of its analysis is a postcolonial feminist. The identity of women’s resistance is a subaltern, where their struggle goes beyond a rejection of the gold mining corporation. The study shows that the direction of resistance is leading to food sovereignty. To maintain their endanger living space, the women's troop is only connected by oral speeches of tradition. The postcolonial feminist analyzes dis/interconnectivity between the interests of the state, local-national-global economic-political linkages. The study shows that the women are agencies in caring for natural resources.